2023
DOI: 10.31234/osf.io/e6px5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does semantic similarity affect immediate memory for order? Usually not, but sometimes it does

Abstract: Recall performance in working memory (WM) is strongly affected by the similarity between items. When asked to encode and recall list of items in their serial order, people confuse more often the position of similar compared to dissimilar items. Models of WM explain this deleterious effect of similarity through a problem of discriminability between WM representations. In contrast, when lists of items that are all semantically similar are compared to lists of dissimilar items, semantic similarity does not negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Subsequent experiments have replicated these results in the phonological and visuospatial domains (Kowialiewski, Lemaire, et al, 2022). A recent work of our own (Kowialiewski, Majerus, et al, 2023) showed that the effect replicates regardless of presentation modality (i.e., auditory, written), and test method (i.e., serial recall, order reconstruction). Furthermore, the increased of within-category transpositions is not due to participants developing long-term memory knowledge or expectations about the semantic list structure during the experimental setup, as the effect persists when participants cannot predict the lists' semantic structures, suggesting a non-strategic origin.…”
Section: Benchmark #6: Semantic Similarity Constrains Order Errorsmentioning
confidence: 56%
See 4 more Smart Citations
“…Subsequent experiments have replicated these results in the phonological and visuospatial domains (Kowialiewski, Lemaire, et al, 2022). A recent work of our own (Kowialiewski, Majerus, et al, 2023) showed that the effect replicates regardless of presentation modality (i.e., auditory, written), and test method (i.e., serial recall, order reconstruction). Furthermore, the increased of within-category transpositions is not due to participants developing long-term memory knowledge or expectations about the semantic list structure during the experimental setup, as the effect persists when participants cannot predict the lists' semantic structures, suggesting a non-strategic origin.…”
Section: Benchmark #6: Semantic Similarity Constrains Order Errorsmentioning
confidence: 56%
“…The effect was only half as large in the interleaved condition. Results from a recent replication (Kowialiewski, Majerus, et al, 2023, Experiment 1) are illustrated in Figure 5. As can be seen, the separation effect has a beneficial effect on item recall (left panel).…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations